2009
DOI: 10.1021/pr900289g
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Apoptosis-Evasion Proteins/Pathways in Human Hepatoma Cells via Induction of Cellular Hormesis by UV Irradiation

Abstract: Evading apoptosis is pivotal in both of carcinogenesis and resistance to anticancer therapy. We investigated the molecules and pathways of apoptosis evasion in human hepatoma cells by irradiating hepatoma cells with optimized UV (so-called "hormetic responses"). Proteins and pathways related to hormetic responses were identified via proteomic approaches followed by reconstruction of function-networks. Of the 2326 defined protein spots, 42 distinct proteins significantly changed their expression. Eleven hormeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 39 publications
3
25
0
Order By: Relevance
“…This caused endoplasmic reticulum stress in the neuroblastoma cells which eventually led to the initiation of cell death [38]. Likewise, the up-regulation of UCH-L1 in human hepatoma cells following low dose UV irradiation was reported to be involved in the regulation of cell death by inhibition of p53-mediated apoptosis; hence in both these cases UCH-L1 was demonstrated to be an "apoptosis-evading protein" [39], as in the present study.…”
Section: Discussionsupporting
confidence: 55%
“…This caused endoplasmic reticulum stress in the neuroblastoma cells which eventually led to the initiation of cell death [38]. Likewise, the up-regulation of UCH-L1 in human hepatoma cells following low dose UV irradiation was reported to be involved in the regulation of cell death by inhibition of p53-mediated apoptosis; hence in both these cases UCH-L1 was demonstrated to be an "apoptosis-evading protein" [39], as in the present study.…”
Section: Discussionsupporting
confidence: 55%
“…Nucleophosmin, nucleolin and fibrillarin are major multifunctional nucleoproteins participating in rRNA processing and ribosome biogenesis [18]. Nucleophosmin, a 37-kDa phosphoprotein, plays a pivotal role in protecting cells from death in response to cell stress [45]. Various cellular activities have been attributed to it, including cell proliferation [46], nucleic acid binding, ribonuclease, molecular chaperone [47] and response to stress-stimuli [48].…”
Section: Resultsmentioning
confidence: 99%
“…Apart from these preclinical findings, evidence for a key role of CerK in tumor progression was reported by Ruckhäberle et al [47], who demonstrated that high CerK expression in tumor tissues correlated with a worse prognosis in patients with estrogen receptor-negative breast cancer. Moreover, recent data also suggest that the CerK protein is upregulated as a hormetic response of hepatoma cells exposed to UV irradiation to evade apoptosis, which could be counteracted by CerK silencing [48]. Based on this observation, pharmacological inhibition of CerK was suggested as a new concept in hepatoma therapy.…”
Section: Discussionmentioning
confidence: 99%